Dual role of miR-1 in the development and function of sinoatrial cells. (August 2021) - Benzoni, P.; Nava, L.; Giannetti, F.; Guerini, G.; Gualdoni, A.; Bazzini, C.; Milanesi, R.; Bucchi, A.; Baruscotti, M.; Barbuti, A.
Abstract: miR-1, the most abundant miRNA in the heart, modulates expression of several transcription factors and ion channels. Conditions affecting the heart rate, such as endurance training and cardiac diseases, show a concomitant miR-1 up- or down-regulation. Here, we investigated the role of miR-1 overexpression in the development and function of sinoatrial (SAN) cells using murine embryonic stem cells (mESC). We generated mESCs either overexpressing miR-1 and EGFP (miR1OE) or EGFP only (EM). SAN-like cells were selected from differentiating mESC using the CD166 marker. Gene expression and electrophysiological analysis were carried out on both early mES-derived cardiac progenitors and SAN-like cells and on beating neonatal rat ventricular cardiomyocytes (NRVC) over-expressing miR-1. miR1OE cells increased significantly the proportion of CD166 + SAN precursors compared to EM cells (23% vs 12%) and the levels of the transcription factors TBX5 and TBX18, both involved in SAN development. miR1OE SAN-like cells were bradycardic (1, 3 vs 2 Hz) compared to EM cells. In agreement with data on native SAN cells, EM SAN-like cardiomyocytes show two populations of cells expressing either slow- or fast-activating If currents; miR1OE SAN-like cells instead have only fast-activating If with a significantly reduced conductance. Western Blot and immunofluorescence analysis showed a reduced HCN4 signal in miR-1OE vs EM CD166+ precursors. Together these data point out to a specific down-regulation of the slow-activating HCN4 subunit by miR-1. Importantly, the rate and If alterations were independent of the developmental effects of miR-1, being similar in NRVC transiently overexpressing miR-1. In conclusion, we demonstrated a dual role of miR-1, during development it controls the proper development of sinoatrial-precursor, while in mature SAN-like cells it modulates the HCN4 pacemaker channel translation and thus the beating rate. Graphical abstract: Unlabelled Image Highlights: miR-1 increase SAN-specific transcription factors and the number of SAN precursors during sinus node development Silencing miR-1 impair spontaneous contraction in mESC-derived embryoid bodies. miR-1 slows the beating rate of pacemaker cells by inhibiting HCN4 translation and thus reducing the If current miR-1 Overexpression accelerate If activation kinetics and decreases cAMP response compatibly with a decreased HCN4/HCN1